Urgency of controlling black carbon emissions in shipping - Ong, Min Yee (Nanyang Technological University, 2022)
There has been a lot of discussion about sustainable shipping and decarbonisation in the maritime industry. The IMO 2020 sulphur cap was a big stride towards green shipping. However, there is still a significant amount of work that needs to be completed before the industry can be fully sustainable and carbon free. Climate change has been the main driver of greener shipping especially since it has opened up the Arctic trade routes for longer periods of time. With more ships sailing through the Arctic, significant damages to its natural ecosystem may arise due to BC emissions. However, questions on whether BC is a legitimate threat to the environment continue to be raised by stakeholders. Hence, this study seeks explores the impacts of BC on a regional and global scale and understand the challenges faced in BC reduction to establish the legitimacy of BC as a climate threat and determine the urgency in reducing BC emissions from ships.